RAB11FIP1: An Indicator for Tumor Immune Microenvironment and Prognosis of Lung Adenocarcinoma from a Comprehensive Analysis of Bioinformatics - Zhang, Wenyi; Chen, Ting; Liu, Jun; Yu, Shali; Liu, Lei; Zheng, Miaosen; Liu, Yifei; Zhang, Hongbing; Bian, Tingting; Zhao, Xinyuan (Frontiers in Genetics, 2021)
Lung adenocarcinoma (LUAD) has always been the first one all over the world. RAB11FIP1 was found to be expressed differently in a critical way among different cancers. However, the prognostic value and immune infiltration of RAB11FIP1 expression in LUAD still remains to be unclear. In this study, the expression of RAB11FIP1 in LUAD was investigated in Oncomine, TCGA and UALCAN databases. Kaplan-Meier analysis was chosen to compare the association between RAB11FIP1 expression and overall survival (OS) in LUAD patients. The dataset of TCGA was retrieved and analyzed the pertinence between RAB11FIP1 and clinicpathological factors. LncRNA-miRNA-mRNA ceRNA network was constructed to explore the insight underlying the relationship between RAB11FIP1 and LUAD. GO, KEGG, and network analysis of protein-protein interactions (PPI) were conducted to investigate the potential mechanism of RAB11FIP1. In the end, the relevance of RAB11FIP1 to cancer immune infiltrates was investigated. RAB11FIP1 was found down-regulated by tumors compared with adjacent normal tissue in multiple LUAD cohorts. RAB11FIP1 expression was associated with tumor size and stage. There was high correlation between low RAB11FIP1 in tumors and worse OS in LUAD. Functional network analysis suggested that RAB11FIP1 was associated with multiple pathways. Besides, the expression of RAB11FIP1 was closely related to the infiltration levels of B cell, CD8+ T cells, CD4+ T cells, macrophages, neutrophils and dendritic cells. RAB11FIP1 expression in LUAD was occurred with a variety of immune markers. Our findings suggest that RAB11FIP1 is related to prognosis and immune infiltrates in LUAD.